Central pontine myelinolysis: not just a low sodium issue - Titus, Gideon; Vazi, Luthando; Sabela, Tholakele; Chothia, Mogamat-Yazied (African Journal of Nephrology, 2020)
Osmotic demyelination syndrome is a rare complication following treatment of chronic hyponatraemia. We describe a case of a middle-aged man known with hypertension and hypothyroidism who presented with a reduced level of consciousness and a generalised convulsion. Laboratory results revealed severe hyponatraemia and hypokalaemia. Following rapid overcorrection of the serum sodium concentration, his level of consciousness remained unchanged, and he developed quadriplegia. Magnetic resonance imaging of the brain revealed central pontine myelinolysis (CPM). The patient died 3 weeks after hospitalisation. Other than rapid overcorrection of chronic hyponatraemia, this case also highlights the important role of potassium in the pathogenesis of CPM. Therefore, when severe chronic hyponatraemia is accompanied by hypokalaemia, the latter should be corrected first to further reduce the risk of CPM.